HPLC-ESI-IT-MS/MS Analysis and Biological Activity of Triterpene Glycosides from the Colombian Marine Sponge Ectyoplasia ferox - Colorado-Ríos, Jhonny (MDPI, 2013)
The marine sponge Ectyoplasia ferox produces antipredatory and allelopathic triterpenoid glycosides as part of its chemical defense repertoire against predators, competitors, and fouling organisms. These molecules are responsible for the pharmacological potential found in the glycosides present in this species. In order to observe the glycochemical diversity present in E. ferox, a liquid chromatography coupled to a tandem mass spectrometry approach to analyse a complex polar fraction of this marine sponge was performed. This gave valuable information for about twenty-five compounds three of which have been previously reported and another three which were found to be composed of known aglycones. Furthermore, a group of four urabosides, sharing two uncommon substitutions with carboxyl groups at C-4 on the terpenoid core, were identified by a characteristic fragmentation pattern. The oxidized aglycones present in this group of saponins can promote instability, making the purification process difficult. Cytotoxicity, cell cycle modulation, a cell cloning efficiency assay, as well as its hemolytic activity were evaluated. The cytotoxic activity was about IC(50) 40 µg/mL on Jurkat and CHO-k(1) cell lines without exhibiting hemolysis. Discussion on this bioactivity suggests the scanning of other biological models would be worthwhile.